Contrasting crystal packing arrangements in triiodide salts of radical cations of chiral bis(pyrrolo[3, 4-d])tetrathiafulvalenes1. Issue 38 (14th October 2015) - Martin, Lee; Yang, Songjie; Brooks, Andrew C.; Horton, Peter N.; Male, Louise; Moulfi, Ourida; Harmand, Lydie; Day, Peter; Clegg, William; Harrington, Ross W.; Wallis, John D.
<x xml:space="preserve">Abstract</x> Triiodides are arranged in head to tail pairs, infinite lines or a castellated arrangement in the radical cation salts of chiral bis(N(1-arylethyl))pyrrolo-tetrathiafulvalene salts.